EFL teachers attitudes towards information and communication technologies (ICT) - Kızıl, Aysel Şahin (My University, 2011)
Depending on the fact that teachers’ attitude is a major predictor in the process of ICT integration, this study investigated the ICT usage and the attitudes of high school EFL teachers in Turkey towards ICT. Additionally, this study focused on the relationship between computer attitudes and extension of ICT usage, computer attributes and personal characteristics. The data gathered through a questionnaire from in-service EFL teachers (n=76) working at state schools were analysed by using descriptive statistics and Pearson Correlations. The findings suggest that the most widely used ICT tools are gradebook, internet, software for repetitive practice, processing texts, interactive exercises and PowerPoint presentations. It was also found that EFL teachers hold positive attitudes towards the use of ICT for educational purposes: they regard computers as advantageous over traditional methods of instruction and suitable for their curriculum goals. However, the responses indicate that insufficient class time and inadequate training opportunities are the major obstacles in the process of ICT integration.
Bildiri - Yayımlanmış
Keywords: EFL; ICT; Technology integration; Diffusion of innovations